2013
DOI: 10.1007/s10585-013-9606-5
|View full text |Cite
|
Sign up to set email alerts
|

Combination of percutaneous radiofrequency ablation and systemic chemotherapy are effective treatment modalities for metachronous liver metastases from gastric cancer

Abstract: This study evaluated the efficacy of percutaneous radiofrequency ablation (RFA) for the treatment of metachronous liver metastases of gastric cancer. We enrolled a total of 44 patients who underwent percutaneous RFA for the treatment of metachronous liver metastases after resection of a primary gastric adenocarcinoma from January 2002 to November 2011. The primary endpoint of this study was overall survival (OS) and recurrence-free survival (RFS) after RFA. Systemic chemotherapy was combined with RFA in 40 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…In comparison, 43.4% (33/76) patients in chemotherapy group had multiple liver metastases, 36.8% (28/76) with extrahepatic metastases, and the largest size was 6.7 cm. In univariate analysis, size, number, and extrahepatic metastases were identified as prognostic factors for survival, which was in consistent with previous studies regarding RFA for LMGC [2,13,29]. Additionally, studies regarding hepatectomy for LMGC also revealed prognostic value of size and number of LMGC [24,36].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In comparison, 43.4% (33/76) patients in chemotherapy group had multiple liver metastases, 36.8% (28/76) with extrahepatic metastases, and the largest size was 6.7 cm. In univariate analysis, size, number, and extrahepatic metastases were identified as prognostic factors for survival, which was in consistent with previous studies regarding RFA for LMGC [2,13,29]. Additionally, studies regarding hepatectomy for LMGC also revealed prognostic value of size and number of LMGC [24,36].…”
Section: Discussionsupporting
confidence: 88%
“…It is reported that around 5-9% patients may develop liver metastases from gastric cancer (LMGC), and surgical resection is the optimal treatment [2]. However, the resection rate for LMGC is just 1.4-21.1% [3].…”
Section: Introductionmentioning
confidence: 99%
“…RF ablation should be considered as an alternative treatment option to surgical resection of hepatic metastases from gastric cancer. Several reports on RF ablation therapy for hepatic metastasis from gastric cancer and its clinical outcomes were published more recently (6)(7)(8). For the first time, Kim et al (6) The OS in the present study was better than that reported previously.…”
Section: Discussionsupporting
confidence: 40%
“…More recently, RF ablation was used for the treatment of liver metastases from gastric cancer after surgical treatment of the primary tumor and produced variable median survival periods ranging from 10.0 to 20.9 months with better survival outcomes in cases with single, small, and unilobar hepatic metastases (6)(7)(8). These results suggested that RF ablation could be an alternative treatment option for patients with metastases from gastric cancer that are confined to the liver.…”
mentioning
confidence: 99%
“…Although few studies have examined DTA, several have reported on the combination of cryoablation or heat thermal therapy with other methods, including radiation, chemotherapy (e.g. FOLFIRINOX) and excision, yielding improved outcome [15,[41][42][43][44][45]. As such, we examined the combination of heat and freezing on PaCa.…”
Section: Discussionmentioning
confidence: 99%